Peran PENMAS POLDA SUMSEL dalam Menyampaikan Informasi KAMTIBMAS di Sumatera Selatan - Lady, Nadia; Hamidah; Hamandia, Muhammad Randicha (Pubmedia Social Sciences and Humanities, 2024)
This research is entitled "The Role of South Sumatra POLDA PENMAS in Conveying KAMTIBMAS Information in South Sumatra". The South Sumatra Regional Police conveyed information on social security and order via talk shows on radio stations in Palembang, South Sumatra. The presence of the police cannot be separated from the supra system that surrounds it, namely society. From various publications discussing police challenges, it can be concluded that there is a connection between the role of the police and community development. Therefore, the workload and role of the police always changes from time to time. The main tasks of the police in historical development revolve around enforcing the law (law enforcement), maintaining public order (order maintenance or peacekeeping) as well as providing community service and also maintaining internal security. This research aims to determine the role of Penmas at the South Sumatra Regional Police in conveying National Security Information in South Sumatra. The research method used is this research uses a research method with a qualitative approach. The Qualitative Approach is research where the researcher in conducting the research uses observation techniques, interviews, content analysis, and other data collection methods to present the subject's responses and behavior. The results of this research are: As a liaison for organizations or institutions represented by the public, namely being a liaison in conveying information to internal and external parties, playing a role in conveying information on social security and order in South Sumatra. As people who take part in social interactions, we strive to foster positive and mutually beneficial relationships with the public and build a safe and orderly environment in South Sumatra. So the role of Penmas is in conveying information on social security and order. That Penmas has carried out its duties and responsibilities in accordance with its role and function in conveying information to Kamtibmas.